Endovascular Treatment of Internal Iliac Artery Aneurysms: Single Center Experience - Machado, R. (2016)
Objective: Internal iliac artery aneurysms (IIAA) are rare, representing only 0.3% of aortoiliac aneurysms. Its treatment with open surgery is complex and associated with high morbidity and mortality, which led to increasing application of endovascular solutions. In this study, we aimed to evaluate outcomes of endovascular aneurysm repair (EVAR) of IIAA in one institution. Methods: We retrospectively reviewed all cases of IIAA treated with endovascular techniques between 2003 and 2014. Endpoints were morbidity, mortality, freedom from pelvic ischemic symptoms (buttock claudication, ischemic colitis, and spinal cord injury), and need for reintervention. Results: There were 16 patients, 13 males and 3 females, with mean age of 75.1±7 years. A total of 20 IIAA (4 cases were bilateral), with mean diameter of 37.9 mm, were treated. EVAR was performed in 13 (81.3%) patients, with associated internal iliac artery's outflow occlusion in 2. Iliac branch device was used in one patient. Two patients underwent endovascular IIAA embolization alone. One patient underwent percutaneous, transgluteal, IIAA embolization. IIAA flow preservation in at least one internal iliac artery was possible in 9 (56.3%) patients. Early mortality was 7% (1 case). Early morbidity was 18.8%. Pelvic ischemic complications occurred in 1 (7%) patient with buttock claudication. Late reintervention was needed in 3 patients, none of them for IIAA related complications. Conclusion: Endovascular treatment of IIAA is technically feasible and durable. Although overall morbidity is relatively high, major complications are infrequent and perioperative mortality is low. internal iliac artery flow preservation is technically challenging and, in a significant number of cases, not possible at all.